Implementasi Energi Terbarukan berupa Penerangan Jalan Umum Berbasis Tenaga Surya di Desa Buniwangi Surade Sukabumi - Falentino Sembiring; Wahyu Irwan Putra; Ibnu Ngatoilah; Atto Mustopa (Jurnal Pengabdian Kepada Masyarakat Abdi Putra, 2023)
Lighting is an important part for humans in carrying out activities at night but in some areas, there are still frequent blackouts. Solar-based public street lighting can be alternative lighting when the lights go out. Renewable energy produced by solar power is a cheap alternative and can be used to become an efficient energy source. The village of buniwangi has several locations that are still poorly lit, so the village of buniwangi was chosen to be the place of choice.